Thomas Hunt's Monograms. (8th September 2021) - Adams, Jenny
Abstract: This note expands on an article by Malcolm Parkes, published posthumously in The Library . In his article, Parkes looks at monograms left by Oxford stationer Thomas Hunt in the manuscripts that Hunt appraised. He argues that Hunt capitalized on these manuscripts, using them as securities for borrowed money he in turn invested in his printing business. Thos note shows that Hunt appraised several more books than Parkes found and suggest that Hunt's work as a university stationer was possibly more lucrative than previously imagined.